Monte-Carlo Stimulation for European Rainbow Call Options BASED on Meta and NEM’s Case Study - Ding, Xilong (BCP Business & Management, 2022)
Recently, investors have paid great attention to the metaverse sector and the investing instruments for metaverse. Metaverse has become the most popular investment sector since 2021. Due to the rapid development of the industry, coupled with the social instability, it is critical to search for the appropriate investment. Previous literature proposed many advantages of the rainbow options and the expected growth of the metaverse industry. However, there is currently a lack of research on the combination of metaverse assets and the rainbow options. Based on this, this paper chooses the stocks of the metaverse enterprise META and the gold enterprise NEM as the safe-haven asset to construct a two-color European rainbow call options and chooses yahoo Finance’s transaction data and excel and python as analysis software. The rainbow options return is given by Monte Carlo simulation method, and complete sensitivity analysis of the four parameters. At the end, the pros cons of rainbow options are compared. Besides three findings are obtained, including that options have cost advantages, could gain return from the market volatility by changing the portfolio, and have sharp peaks and thick tails in the distribution.